2013
DOI: 10.1007/s11010-013-1856-7
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to fibronectin induces p27Kip1 nuclear accumulation through down-regulation of Jab1 and contributes to cell adhesion-mediated drug resistance (CAM-DR) in RPMI 8,226 cells

Abstract: Mounting evidence has been shown that integrin-mediated cellular adhesion confers resistance to chemotherapy of multiple myeloma. The molecular mechanism underlying cell adhesion-mediated drug resistance (CAM-DR) is, however, poorly understood. In this report, we demonstrated that RPMI 8,226 cells accumulated p27(Kip1) in the nucleus when they were adhered to fibronectin (FN). The adhesion-mediated p27(Kip1) nuclear recruitment was regulated via the down-regulation of Jab1, a negative regulator of cell cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Previously, our laboratory has discovered that adhesion of multiple myeloma cells to FN can confer a form of drug resistance, and the adhesion status of MM cells may be of outstanding significance for their response to therapeutic drugs (30,31,37) . In this research the relationship between VRK1 expression and adhesive ability of MM cells was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our laboratory has discovered that adhesion of multiple myeloma cells to FN can confer a form of drug resistance, and the adhesion status of MM cells may be of outstanding significance for their response to therapeutic drugs (30,31,37) . In this research the relationship between VRK1 expression and adhesive ability of MM cells was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we showed that adhesion to FN decreased TRIP6 expression, thereby increasing nuclear p27 Kip1 expression via decreasing phosphorylation of p27 Kip1 at T157. As nuclear p27 Kip1 expression is closely associated with CAM-DR phenotype [6], we then proceeded to investigate whether manipulation of TRIP6-mediated pT157-p27 Kip1 levels had any effect on the CAM-DR phenotype. Intriguingly, cell cycle progression induced by TRIP6 was also arrested or accelerated when transfected with myc-T157A or myc-T157D, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study demonstrated that knockdown of TRIP6 in glioblastoma or ovarian cancer can elevate nuclear p27 Kip1 expression [10]. As we know, adhesion of tumor cells to FN can induce cell cycle arrest and protect tumor cells from chemotherapeutic drug-induced apoptosis via increasing nuclear p27 Kip1 protein expression [5,6]. Consequently, we asked whether TRIP6 overcame CAM-DR phenotype by regulating nuclear p27 Kip1 expression.…”
Section: Trip6 Knockdown Upregulates Nuclear P27 Kip1 Expressionmentioning
confidence: 97%
See 1 more Smart Citation
“…is thought to be a major obstacle in the treatment of myeloma (13,(22)(23)(24)(25). To investigate the role of Homer1b/c in CAM-DR, we built the MM cell adhesion model, in which RPMI-8226 and U266 cells were adherent to the FN and HS-5 cells (3).…”
Section: The Expression Of Homer1b/c Associated With Cell Adhesion Inmentioning
confidence: 99%